Hepatitis C Treatment in Patients with Porphyria Cutanea Tarda - Singal, Ashwani K (Am J Med Sci, 2017)
BACKGROUND AND AIM: Hepatitis C virus (HCV) infection is a common susceptibility factor for porphyria cutanea tarda (PCT). Experience on HCV treatment in PCT patients is limited. Recently, HCV treatment has improved with direct acting antivirals (DAA). We review our experience on HCV treatment in PCT patients with older and newer regimens. METHODS: HCV treatment was attempted 22 times in 13 PCT patients (five attempts in one, two in 5 and one in the other 7 patients). RESULTS: Before starting HCV treatment, PCT was in complete remission in 16, partial remission in 2, unknown status in 2, and active in 2 instances. PCT relapsed during therapy 6 times (all interferon based regimens, 2 including telaprevir), four requiring treatment interruption. Treatment was interrupted for reasons other than PCT relapse in 2 patients treated with interferon based regimens. To prevent PCT recurrence, HCQ was continued during HCV therapy 6 times (3 interferon regimens, 2 ribavirin regimens without interferon, and one DAA alone). Twelve patients achieved sustained viral response (SVR), 3 with interferon regimens and 9 with DAA. Two patients with active PCT were treated with DAA, with reduction of plasma porphyrins in one and normalization in the other at the end of HCV therapy. CONCLUSION: HCV treatment regimens including interferon or ribavirin may precipitate PCT relapse. HCQ may be useful to prevent such relapses. In this limited experience, DAA were not associated with PCT relapse. Studies are needed to examine DAA as primary PCT treatment in HCV-infected patients.